2018
DOI: 10.3892/mmr.2018.8668
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential genes and miRNAs associated with sepsis based on microarray analysis

Abstract: Sepsis is a type of systemic inflammatory response syndrome caused by infection. The present study aimed to examine key genes and microRNAs (miRNAs) involved in the pathogenesis of sepsis. The GSE13205 microarray dataset, downloaded from the Gene Expression Omnibus was analyzed using bioinformatics tools, and included muscle biopsy specimens of 13 patients with sepsis and eight healthy controls. The differentially expressed genes (DEGs) in samples from patients with sepsis were identified using the Linear Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…MiRNAs, which are a class of non‐coding nucleotide single‐stranded small‐molecule RNAs, participate in various biological processes such as cell proliferation, differentiation and apoptosis . In recent years, studies have found that miRNA could be used as a new biomarker in the diagnosis of sepsis . Researcher found that serum miR‐574 could be used as a predictor of prognosis in patients with sepsis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs, which are a class of non‐coding nucleotide single‐stranded small‐molecule RNAs, participate in various biological processes such as cell proliferation, differentiation and apoptosis . In recent years, studies have found that miRNA could be used as a new biomarker in the diagnosis of sepsis . Researcher found that serum miR‐574 could be used as a predictor of prognosis in patients with sepsis .…”
Section: Introductionmentioning
confidence: 99%
“…12 In recent years, studies have found that miRNA could be used as a new biomarker in the diagnosis of sepsis. [13][14][15] Researcher found that serum miR-574 could be used as a predictor of prognosis in patients with sepsis. 16,17 However, the dynamic expression of miRNA-574 in sepsis has not been reported.…”
mentioning
confidence: 99%
“…24 A number of studies have found that MYC participates in the pathogenesis of sepsis. [25][26][27] Together, these findings suggest that CCAT2 may be involved in the pathology of sepsis. Recent studies have reported that CCAT2 gene polymorphisms are associated with susceptibility to various diseases, such as recurrent miscarriage, endometrial carcinoma and colorectal cancer, [28][29][30] and further research has shown that the rs6983267 polymorphism in the CCAT2 contributes to increases in MYC expression.…”
Section: Introductionmentioning
confidence: 77%
“…[321,322] Interestingly, besides being connected to cancer cell functions, NOP14 has also been shown to constitute a key gene in sepsis and may thus be associated with systemic inflammation. [323] 5.…”
Section: The Cellular Target Of Vioprolide Amentioning
confidence: 99%
“…NOP14 has been reported as potential marker of sepsis, indicating a general involvement in the immune response. [323] Nevertheless, the role of NOP14 in the response towards inflammatory stimuli has not been elucidated, yet. Considering that vioprolide A exerts strong anti-inflammatory actions and targets NOP14 in endothelial cells, a potential connection between these two events is likely.…”
Section: The Involvement Of the Cellular Target Nop14 In The Antiinfl...mentioning
confidence: 99%